Influence of Variable Viscosity on Peristaltic Motion of a Viscoelastic Fluid in a Tapered Microfluidic Vessel - Prakash, J.; P.Siva, E.; Govindarajan, A.; Vidhya, M. (International Journal of Engineering and Technology, 2018)
The peristaltic flow of a viscoelastic fluid in the tapered microchannel with variable viscosity is investigated. This study is reinvigorated by discovering fluid dynamic in peristaltic motion as signified by biological flows, pharmacodynamics and gastro-intestinal motility enhancement. The microchannel non-uniform and asymmetry is developed by choosing a peristaltic wave train on the wall with different amplitudes and phases. The flow analysis has been arisen for low Reynolds number and long wavelength case. The solutions for stream function, axial velocity and pressure gradient are obtained. The effects of pertinent parameters on the average pressure rise per wavelength are investigated by means of numerical integration. The axial velocity and phenomena of trapping are further discussed.Â Â